Schisandra chinensis inhibits the entry of BoHV-1 by blocking PI3K-Akt pathway and enhances the m6A methylation of gD to inhibit the entry of progeny virus - Liu, Yang; Wang, Kang; Gong, Xiao; Qu, Weijie; Xiao, Yangyang; Sun, Hongtao; Kang, Jingli; Sheng, Jinliang; Wu, Faxing; Dai, Feiyan (Frontiers in Microbiology, 2024)
Schisandra chinensis, a traditional Chinese medicine known for its antitussive and sedative effects, has shown promise in preventing various viral infections. Bovine herpesvirus-1 (BoHV-1) is an enveloped DNA virus that causes respiratory disease in cattle, leading to significant economic losses in the industry. Because the lack of previous reports on Schisandra chinensis resisting BoHV-1 infection, this study aimed to investigate the specific mechanisms involved. Results from TCID50, qPCR, IFA, and western blot analyses demonstrated that Schisandra chinensis could inhibit BoHV-1 entry into MDBK cells, primarily through its extract Methylgomisin O (Meth O). The specific mechanism involved Meth O blocking BoHV-1 entry into cells via clathrin- and caveolin-mediated endocytosis by suppressing the activation of PI3K-Akt signaling pathway. Additionally, findings from TCID50, qPCR, co-immunoprecipitation and western blot assays revealed that Schisandra chinensis blocked BoHV-1 gD transcription through enhancing m6A methylation of gD after virus entry, thereby hindering gD protein expression and preventing progeny virus entry into cells and ultimately inhibiting BoHV-1 replication. Overall, these results suggest that Schisandra chinensis can resist BoHV-1 infection by targeting the PI3K-Akt signaling pathway and inhibiting gD transcription.